Feature writing for filipinos - Genove, Maria Cecilia M; Maslog, Crispin C. (Quezon City, 2004)
In general and en toto, this is an excellent bok that can be the first feature writing, textbook for Filipinos written by a Filipino. It is a textbook that is badly needed in the Philippines, where most of our communication textbooks and references are written by foreigners and imported. It is a book whose time has gone. As a whole, the book is well written, like a good, interesting feature story. The style is delightfully fluent, clear, concise, and extremely readabl. It contains everything of what a students need to know about feature writitng based on the writer's experience and years of research on the subject. It seems that the writer has poured her heart and soul into this piece of work.
Keywords: Feature Writing